Numerical Analysis in DFT and SCAPS-1D on the Influence of Different Charge Transport Layers of CsPbBr3 Perovskite Solar Cells - Hossain, M. Khalid; Mohammed, Mustafa K. A.; Pandey, Rahul; Arnab, A. A.; Rubel, M. H. K.; Hossain, K. M.; Ali, Md Hasan; Rahman, Md. Ferdous; Bencherif, H.; Madan, Jaya; Islam, Md. Rasidul; Samajdar, D. P.; et al. (Energy & fuels, 2023)
The power conversion efficiency (PCE) of cesium lead halide (CsPbX3, X = l, Br, and Cl)-based all-inorganic perovskite solar cells (PSCs) is still struggling to compete with conventional organic–inorganic halide perovskites. A combined material and device-related analysis is much needed to understand the working principle to explore the efficiency potential of CsPbX3-based PSCs. Therefore, here, density functional theory (DFT) and SCAPS-1D-based studies were reported to evaluate the photovoltaic (PV) performance of CsPbBr3-based PSCs. DFT is first applied to assess and extract structural and optoelectronic properties (band structure, density of states, Fermi surface, and absorption coefficient) of the considered absorber layer. The calculated electronic band gap (E g) of the CsPbBr3 absorber was 1.793 eV, which matched well with the earlier computed theoretical value. Additionally, the Pb 6p orbital contributed largely to the calculated density of states (DOS), and the electronic charge density map showed that the Pb atom acquired the majority of charges. In order to examine the optical response of CsPbBr3, optical characteristics were computed and correlated with electronic properties for its probable photovoltaic applications. Fermi surface computation showed multiband characters. Furthermore, to look for a suitable combination of the charge transport layer, a total of nine HTLs (Cu2O, CuSCN, P3HT, PEDOT:PSS, Spiro-MeOTAD, CuI, V2O5, CBTS, and CFTS) and six ETLs (TiO2, PCBM, ZnO, C60, IGZO, and WS2) are used considering the experimental E g (2.3 eV). The best power conversion efficiency (PCE) of 13.86% is reported for TiO2 and CFTS in combination with the CsPbBr3 absorber. The effects of operating temperature, series and shunt resistances, Mott–Schottky, capacitance, generation and recombination rates, quantum efficiency, and current–voltage density were also examined. The resulting PV properties were also compared with previously published data. Results reported in this study will pave the way for the development of high-efficiency all-inorganic CsPbBr3-based solar cells in the future.